Potential reservoirs of a 'Candidatus Phytoplasma pruni'-related strains (16SrIII-X) associated with HLB-like symptoms in citrus in Brazil - Barbosa, Julio C.; Gasparoto, Maria C. G. [UNESP]; Eckstein, Barbara; Bergamin Filho, Armando; Bedendo, Ivan P. (Springer, 2020)
Plants of beggarticks (Bidens pilosa L.), honeyweed (Leonurus sibiricus L.), and citrus (Citrus ssp.) trees exhibiting phyllody and virescence, leaf distortion, and yellow shoots symptoms, respectively, were found in orchards at the state of Sao Paulo. Based on PCR assays, computer-simulated RFLP, and phylogenetic analyses, it was confirmed that these plants were infected with a phytoplasma of the subgroup 16SrIII-X, belonging to the 'Candidatus Phytoplasma pruni' species. This finding suggested that beggartick and honeyweed plants may be possible reservoirs of 16SrIII-X phytoplasma to citrus tree. The phytoplasma identified in this study presented perfect identity with the phytoplasma previously reported in association with citrus plants harboring HLB-like symptoms, in Brazil.
Keywords: Citrus diseases; Phytopathogenic mollicutes; Fastidious bacteria; Yellows diseases